Effectiveness Test of Several Media For Propagation Biological Agent Trichoderma sp. - Safitri, Novi; Erfandari, Ovy; Nurmayanti, Sri (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2023)
The ecology is negatively impacted by conventional farming methods that keep using more chemicals. Reducing the usage of chemicals is one strategy to combat these adverse effects. Trichoderma sp. is a type of organic fertilizer and pesticide that is beginning to be used extensively. A fungus called Trichoderma sp. is present in all types of soil. Technology is required to mass produce Trichoderma sp. on various types of media because its limited mass manufacturing makes its usage on a broad scale still needs to be completed. This study aims to evaluate the suitability of various mediums as propagation vehicles for Trichoderma species. The State Polytechnic of Lampung's Plant Laboratory conducted this study using a completely randomized design with 5 media treatments. Each treatment consisted of 4 replications. The propagation media used in this study were PDA media as a control, bran, sawdust, corn and rice. The results showed that the most effective growth media for Trichoderma sp. was bran media. The growth of Trichoderma sp. on bran media after 4 days of incubation was 100%. The average number of conidia of Trichoderma sp. the highest was found in bran media, which was 1.17 × 103/g of media.